2014
DOI: 10.21149/spm.v56i3.7346
|View full text |Cite
|
Sign up to set email alerts
|

Validación de un punto de corte para la versión breve de la Escala de Depresión del Centro de Estudios Epidemiológicos en adultos mayores mexicanos

Abstract: Objective. To identify a valid cutoff point associated with Center for Epidemiologic Studies, Depression Scale (CES-D) of seven items, which allows the classification of older adults according to presence/absence of clinically significant depressive symptoms. Materials and methods. Screening study with 229 older adults residing in two states of Mexico (Morelos and Tlaxcala), which were part of the sample from the National Survey of Health and Nutrition, 2012. We estimated the sensitivity and specificity associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 35 publications
0
18
0
2
Order By: Relevance
“…Different cut-offs are recommended, specific for each scale or instrument, to assess the severity of MH disorders, and to distinguish people who would be very likely to be diagnosed with a MH disorder from those with less severe MH symptoms. Although for some instruments the cut-off points are still unclear [61], there are now many instruments that have been validated and for which high degrees of sensitivity have been demonstrated [62,63]. In consequence, studies like Zang et al [54] have demonstrated significantly different associations of PA with MH for individuals with self-reported but not-clinically relevant symptoms, and for those with clinically relevant symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Different cut-offs are recommended, specific for each scale or instrument, to assess the severity of MH disorders, and to distinguish people who would be very likely to be diagnosed with a MH disorder from those with less severe MH symptoms. Although for some instruments the cut-off points are still unclear [61], there are now many instruments that have been validated and for which high degrees of sensitivity have been demonstrated [62,63]. In consequence, studies like Zang et al [54] have demonstrated significantly different associations of PA with MH for individuals with self-reported but not-clinically relevant symptoms, and for those with clinically relevant symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…To measure this variable, we used the brief seven-item version of the Center for Epidemiologic Studies Depression Scale [CES-D]. The Scale covers five dimensions: dysphoric mood, motivation, concentration, loss of pleasure, and sleep disturbance [23] and it has been previously validated in Mexico [24] . The presence of clinically significant depressive symptoms was operationalized according to the total CES-D score, and a dichotomous variable was constructed where 1 (CES-D≥5) indicates the presence of significant symptoms [24] .…”
Section: Methodsmentioning
confidence: 99%
“…The ENSANUT 2018 is a probabilistic representative sample of the Mexican population in all 32 states of Mexico. The ENSANUT 2018 assessed the presence of DS among respondents with the CESD-7, which is a shortened version of the CESD, which includes seven items whose ability to differentiate people with significant DS has been previously documented in the Mexican population (18). Additional details on the methodological design of the ENSANUT 2018 are reported elsewhere (19).…”
Section: Depressive Symptomsmentioning
confidence: 99%